A development of slant path rain attenuation statistic using synthetic storm technique - Hassan, Hasrina (2009)
Frequencies above 10 Ghz has become primary interest nowadays in satellite communication. However, it can be easily distracted due to the rain. Basically the aim for this project is to develop a slant path rain attenuation using Synthetic storm Technique. In this project, a few important parameters which is rain rate series per one minute at selected location is being converted to rain space series at horizontal or slant path using storm translation speed or commercial name “synthetic storm technique”. The prediction was being tested at 11.6GHz at MEASAT-3 satellite with two years rain rate data. Study has been carried out to see how SST prediction model works and its reliable and it physical mathematical approach for developing slant path. This mathematical approach is actually to simply match the long term statistic of rain for example yearly cumulative distribution. An accurate elevation calculation that caused by the environment for the high frequency is needed in order to fully utilized the coverage during rain. The methodologies that have been used in this study were the comprehensive mathematical modeling which is Synthetic storm technique, UTM Semarak is selected location involved in the study also some reference document such as ITU-R document for comparison and referral purposed. This study has succeed to obtain a similar result by comparing to result obtained from previous study done in another country. The findings will help to make the affects of rain become less representatives, in other word, rain will be excluded partially or totally when small sample is available.